Der Tod und die Forelle: New Thoughts on Schubert’s Quintet - Griffel, Michael L. (Current Musicology, 2005)
In the early years of Current Musicology, the only required courses beyond the MA level for PhD students in historical musicology were the two “Research Seminars in Musicology;’ one taught by Denis Stevens and the other by Paul Henry Lang. These courses were designed to engage advanced students in original research, advanced methodology, and significant writing and to prepare them for the qualifying examinations on music history and on theoretical and aesthetic writings in the required languages (French, German, Italian, and Latin). In the fall of 1968, Professor Lang selected as his topic for the research seminar (in which I was enrolled) the symphonies of Franz Schubert. This was the last research seminar given by Professor Lang, who was approaching retirement from Columbia. He divulged to those of us taking the course that in his opinion the three master composers of the tonal era who were most in need of scholarly attention were Handel, Haydn, and Schubert. Lang self-confidently claimed that his recently published study of Handel was setting the record straight on that great composer but that similar work still needed to be done on the other two, and especially on Schubert’s instrumental compositions. The seminar whetted my appetite, and I soon found that Lang was quite right: there was, for example, not a single complete recording of the Schubert symphonies by a major orchestra back in 1968. I decided to write my PhD dissertation on the Schubert symphonies, and so my interest in Schubert’s instrumental music got its start.